2012
DOI: 10.7205/milmed-d-11-00427
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Serum Creatinine and Creatinine-Based Measures of Estimated Glomerular Filtration Rate in an Amputee Population

Abstract: A variety of equations are used to estimate glomerular filtration rate (eGFR). These formulas have never been validated in the setting of traumatic amputation. In this retrospective study involving 255 military personnel with traumatic amputations at a single outpatient center, muscle mass lost was estimated using percentage of estimated body weight lost (% EBWL). Serum creatinine (Scr) and eGFR by the Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Although this could indicate that patients with rhabdomyolysis have better renal function, this is more likely to represent the limitations of creatinine-based measures for eGFR. The higher eGFRs seen in the rhabdomyolysis cohort could be attributable to muscle mass loss and subsequent changes after amputation, such as immobility, low protein intake, or muscle atrophy [20]. Of note, amputations were significantly more common in the group with rhabdomyolysis than in the group without rhabdomyolysis (42.7 vs. 15.4%; p < 0.001).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although this could indicate that patients with rhabdomyolysis have better renal function, this is more likely to represent the limitations of creatinine-based measures for eGFR. The higher eGFRs seen in the rhabdomyolysis cohort could be attributable to muscle mass loss and subsequent changes after amputation, such as immobility, low protein intake, or muscle atrophy [20]. Of note, amputations were significantly more common in the group with rhabdomyolysis than in the group without rhabdomyolysis (42.7 vs. 15.4%; p < 0.001).…”
Section: Discussionmentioning
confidence: 87%
“…Of note, amputations were significantly more common in the group with rhabdomyolysis than in the group without rhabdomyolysis (42.7 vs. 15.4%; p < 0.001). In previous literature, amputations have been shown to lead to overestimation of creatinine-based eGFR, which has been postulated to be a less reliable measure of renal function than eGFR calculated using Cystatin C [20,21]. In addition to a decreased eGFR, a diagnosis of CKD can be made on the basis of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Another predictor of AKI in our model was amputation. Previous work in combat casualties has demonstrated that post-injury creatinine levels are lower in patients with amputations 24,25 , which is likely a result of decreased creatinine production. While this might be expected to decrease the risk of AKI, we observed the opposite to be true.…”
Section: Discussionmentioning
confidence: 94%
“…First, amputees may have undiagnosed CKD due to overestimation of GFR via SCr-based equations [2,3]. Cardiovascular morbidity and mortality are increased in the setting of CKD [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…But, there are exceptions, such as traumatic amputation, where these equations could be less accurate [2,3]. Traumatic amputation is associated with combat, natural disasters, accidents, and acts of violence.…”
Section: Introductionmentioning
confidence: 99%